2015
DOI: 10.1371/journal.pone.0126191
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Professionals’ and Policy Makers’ Views on Implementing a Clinical Practice Guideline of Hypertension Management: A Qualitative Study

Abstract: IntroductionMost studies have reported barriers to guideline usage mainly from doctors’ perspective; few have reported the perspective of other stakeholders. This study aimed to determine the views and barriers to adherence of a national clinical practice guideline (CPG) on management of hypertension from the perspectives of policymakers, doctors and allied healthcare professionals.MethodsThis study used a qualitative approach with purposive sampling. Seven in depth interviews and six focus group discussions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 23 publications
1
41
0
1
Order By: Relevance
“…Regarding these results, Patel et al (2016) state that lack of awareness of practice guidelines and lack of confidence in implementing guidelines are common among care providers, which may influence delivery of nutritional therapy. The findings of the current study seem consistent with results of a study by (Lee et al, 2015) which revealed that barriers to guideline adherence include adopter factors such as lack of awareness, non-familiarity, disagreement, lack of self-efficacy and low outcome expectancy as well as the inertia of previous practice and external barriers.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding these results, Patel et al (2016) state that lack of awareness of practice guidelines and lack of confidence in implementing guidelines are common among care providers, which may influence delivery of nutritional therapy. The findings of the current study seem consistent with results of a study by (Lee et al, 2015) which revealed that barriers to guideline adherence include adopter factors such as lack of awareness, non-familiarity, disagreement, lack of self-efficacy and low outcome expectancy as well as the inertia of previous practice and external barriers.…”
Section: Discussionsupporting
confidence: 90%
“…Unintentional re-admissions would be reflected in the effect of medical results not being suitable sometimes. One approach to advance medical quality is to create guidelines concentrating on medical care quality with the aim of refining the consequences of the medical processes [33].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…When the guideline was available in health facilities, other issues were identified as impeding their use, including language and format of guidelines. Other studies have also identified these features of guidelines as factors that negatively impact utilisation 31–33…”
Section: Discussionmentioning
confidence: 99%